Analisis Yuridis Tindak Pidana Pembunuhan dalam Kasus Pembunuhan di Kampung Gajah - Aurellia Widyadhana; Balqis Safina; Thanya Azura Rianto; Irsyad Ardhiawan Fahrezi; Claudia Angelina Putri; Muhammad Hafiz Maulana Kresno (CV. ITTC INDONESIA, 2026)
Cases of murder involving minors are an important issue to be examined because they are not only related to criminal law aspects but also involve social and psychological factors of the perpetrator. This study aims to analyze the criminal act of murder in the case involving a student of SMPN 26 Bandung, which occurred in the former Kampung Gajah area, West Bandung Regency. This research uses a normative legal research method with statutory and case approaches. The data were obtained through library research sourced from legislation, journals, books, and various news reports relevant to the case under study. The results show that the perpetrator’s actions fulfill the elements of premeditated murder due to the presence of intent and planning before the act was committed. In addition, this case indicates low legal awareness and the influence of social environment factors contributing to the occurrence of the crime. Therefore, preventive efforts are needed through legal education, strengthening the roles of family and school, and strict law enforcement to prevent similar cases from occurring in the future.